(untitled) (Marketing Journal, 2025)
This article explores the implementation of customer relationship management (CRM) systems in developed countries. The experiences of the USA, Japan, and Germany show the impact of CRM technologies on marketing effectiveness, customer loyalty, and service quality. The study analyzes opportunities and prerequisites for applying these systems in Uzbekistan, including infrastructure and digital literacy. Based on global practices, the paper offers recommendations tailored to national conditions. Findings aim t o assist domestic businesses in adopting innovative management strategies. 381